Globalization and its impact on Employment: Evidence from Pakistan - Muhammad Zahir Faridi & Mumtaz Anwar Chaudhry (Journal of Political Studies, 2013)
The core purpose of the analysis is to explore the influence of Globalization on Pakistan’s employment situation. The study is based on time series data covering the period from 1972 to 2010. The study has applied Johansen Cointegration technique to estimate the long run and short run relationship among variables. The results indicate that Globalization has positive and significant impact on employment generation. Further, it is found that health expenditure and national savings have positive influence on employment while population has negative and significance effect on employment. The study suggests that free trade is necessary for employment creation through specialization.